Analisis Kinerja Keuangan Sebelum Dan Sesudah IPO - Desta Suci Ramadayanti; Fauji Sanusi (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study purpose to determine the effect financial performance of companies before and after IPO through financial ratios as measured by Current Ratio, Debt to Equity Ratio, Debt Ratio,, Return On Equity, Return On Asset, Net Profit Margin, and Total Assets Turnover Ratio. The population used in this study is the BEI period 2018. Then using purposive sampling method for selected the sampling, on campanies listed on the IDX period 2018. Method of data analysis used is t test by paired sample T-test. The results of this study found that liquidity ratio, solvency ratio, profitability ratio, and activity ratio, there is a significant relationship before and after IPO, which means H0 accepted .